Analisis Kebijakan Pendidikan dalam Penguatan Adab/Akhlak pada Pendidikan Jarak Jauh (PJJ) Pendidikan Agama Islam - Diyan Haryani; Fitri Oktaviana; Jalaludin Jalaludin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The rapid expansion of digital learning ecosystems has reshaped instructional practices in Islamic Religious Education (PAI), raising concerns about how adab (etiquette) and akhlak (moral character) can be effectively nurtured in Distance Learning (Pembelajaran Jarak Jauh, PJJ). National education policies including the National Education System Law, the Character Education Strengthening Program, the Pancasila Student Profile, the Merdeka Curriculum, and Religious Moderation provide a strong normative basis for integrating moral values into online learning spaces. The purpose of this study is to analyze how these policy frameworks support and direct the strengthening of moral and ethical formation in PAI PJJ. This research employs a qualitative approach using a library research design, drawing on educational regulations from 2020–2023, complemented by academic journals and books. Data were examined through content analysis. The findings show that policy guidelines encourage the incorporation of character-based competencies into digital pedagogical practices, such as the use of learning management systems, moderated online discussions, and affective assessment strategies. However, implementation remains constrained by reduced face-to-face interaction, digital literacy disparities, and challenges in observing and evaluating moral behavior in virtual environments. Despite these obstacles, the study identifies opportunities in ethical digital literacy, constructive e-moderation, and teacher digital exemplarity as strategic pathways for value internalization.